(untitled) (Scholars’ Journal, 2022)
As Aristotle has rightly said that man is a social animal. Social connectivity is must for any human being to develop oneself and to form healthy social relationships in a society. The social intelligence of teachers plays an important role in dealing with students, parents, and other member of society and pre service teachers will consequently join the schools and they will be directly responsible for social development of the children studying there. The aim of present study is to compare the social intelligence of pupil teachers (B. Ed students). The method used in the present study was descriptive survey method. Sampleof the study included B. Ed students of different B. Ed colleges affiliated to Kumaun University Nainital. Mean, SD, t-test were employed to statistically analyze the data. The findings of the study indicate that in some dimensions of social intelligence pupil teachers differ statistically like in patience dimension asit is found that female pupil teachers are more patient that male pupil teachers. In the dimension named cooperativeness male pupil teachers’ score was statistically higher than females. Female pupil teachers were found more able to recognize a social situation than males and, on the dimension, named humour it was shown that male pupil teachers were more humorous than females. Whereas in other dimensions of social intelligence they do not differ statistically namely; sensitivity, confidence, tactfulness and memory and total social intelligence on the basis of gender.